Fraudulent Financial Statement: Implementation of XBRL and Perspective Fraud Hexagon In 5.0 Era - Tri Utami Lestari; Ruri Octari Dinata (AFRE (Accounting and Financial Review), 2024)
This study aims to examine implementation of XBRL and fraud hexagon on the fraudulent financial statement. The purpose of this paper is to determine the influence of implementation of XBRL, stimulus, ego, capability, rationalization, collusion, and opportunity on the fraudulent financial statement. This study employs a quantitative approach to explain the relationship among the variables. The samples in this study is limited to non-financial state-owned companies in Indonesia. The data from non-financial stated-owned enterprises In Indonesia were collected and the analysed through the panel data. Results show that the implementation of XBRL and the fraud hexagon perspective have a simultaneous effect on fraudulent financial statements. This study expands on previous works by investigating the Influence of XBRL Adoption on Financial Reporting Timeliness: Evidence from Indonesian Banking Industry. Such empirical evidence is expected to be used by companies, regulators and researchers in understanding factors that influence financial reporting fraud in non-financial state-owned companies. The samples in this study is limited to non-financial state-owned companies in Indonesia.DOI: https://doi.org/10.26905/afr.v7i2.11912